BER-EUKA KERJA ISLAMI: IBADAH DAN DAKWAH DI TEMPAT KERJA - Nurohman, Aris (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2011)
Islamic work ethic is an Islamic ethic that has been pradiced among the staff base on Islamideaching. islamic work ethic is very important applied in the workplace as a guide staff in performing work in accordance with the values of religious teachings, because the Islamic religion is not only seen as the work of worshipthatwill getthe reward forthe perpetrators, butalso can affedtheformation of a good culture work environment. In this case the ethical work has implications for the effort dakwah bil hal to others in the work environment.